1980
DOI: 10.1099/00207713-30-1-53
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of the Lactobacillus acidophilus Group

Abstract: A total of 89 strains designated Lactobtrcillus acidophilus were examined for physiological properties, type of lactic acid produced, cell wall sugar pattern, guanine plus cytosine content of deoxyribonucleic acid (DNA), and DNA homology values compared with selected reference strains. Immunological reactions among a group of the strains were determined by gel diffusion tests, using antiserum to purified lactic acid dehydrogenase (LDH) from a single strain (Sharpe strain AM). Antiserum to glyceraldehyde-3-phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
117
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(121 citation statements)
references
References 11 publications
3
117
1
Order By: Relevance
“…Miao et al reported a DNA-DNA relative reassociation value of 28% between strains B7gT and B256T (35). In both the work of Miao et al and our work the DNA homology values were below the accepted range (60 t o 100%) for strains belonging to the same species (12,20) but indicated that these species should be assigned to the same genus. Protein electrophoresis results were correlated with DNA-DNA reassociation results, as has been found for other bacteria (12,17).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Miao et al reported a DNA-DNA relative reassociation value of 28% between strains B7gT and B256T (35). In both the work of Miao et al and our work the DNA homology values were below the accepted range (60 t o 100%) for strains belonging to the same species (12,20) but indicated that these species should be assigned to the same genus. Protein electrophoresis results were correlated with DNA-DNA reassociation results, as has been found for other bacteria (12,17).…”
Section: Discussioncontrasting
confidence: 66%
“…DNA was extracted from bacterial cells (2 to 3 g, wet weight) by using the techniques of Marmur (33), except that proteinase K (total weight, 2 mg) was added after cell lysis by lysozyme-SDS and cell lysates were incubated for 3 to 4 h at 37°C to ensure protein degradation. The abilities of DNAs from various organisms to hybridize with one another were determined by John L. Johnson (Department of Anaerobic Microbiology, Virginia Polytechnic Institute and State University), who used the S1 nuclease method (19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Despite considerable industrial and medical interest, the systematics of this species remained confusing for a long time (Moro, 1900;OrlaJensen et al, 1936;Hansen & Mocquot, 1970), and a considerable serological heterogeneity has been shown (Sharpe, 1970;Gasser, 1970). The heterogeneity was also reflected by the results of DNA : DNA hybridization studies (Johnson et al, 1980;Lauer et al, 1980). L. acidophilus and L. gasseri are found in similar habitats and cannot be distinguished by simple phenotypic criteria (Kandler & Weiss, 1986 L. acidophilus DNA similarity groups A4 and B2, respectively (Fujisawa et al, 1992).…”
Section: Introductionmentioning
confidence: 70%
“…This group of bacteria, including L. gasseri, which is found in the human intestine, has been classified on the basis of similarities in rRNA sequences and compositions of the cell walls into six subgroups (9,11,18). Many strains in this group have been shown to be bacteriocin producers (6,12,19,23).…”
mentioning
confidence: 99%